'Mesdames, il faut lire!': Material contexts and representational strategies in early francophone African women's magazines. Issue 2 (January 2016) - Bush, Ruth
Abstract : This article provides the first extended analysis of the earliest francophone African women's magazine, AWA: la revue de la femme noire, founded in Dakar in 1964 by a network of African women. This material predates what is often seen as the 'first generation' of francophone African women writers, harnessing the tropes of glossy magazine culture to test out plural ideas of African femininity. Through this experimentation, and with reference to the practical and symbolic roles of women in post-independence West African nation states (especially Senegal), AWA casts new light on the contribution of women's reading matter and 'popular' print cultures to the production of African modernity in the early post-colonial world. The magazine fuses the dominant gendered tropes of négritude with 1960s consumer culture, new career aspirations, and the everyday lived experience of women from a range of social backgrounds. By restoring this magazine to the global feminist archive, this article situates AWA: la revue de la femme noire as a long overlooked source for tracing the polemical debates concerning the (un)translatability of feminist thought between the global North and global South, post-independence nationalism, and representations of the female body in African and diasporic cultural production.